ENHANCING COMMUNITY LITERACY THROUGH CONTEXTUAL INDONESIAN LANGUAGE INSTRUCTION - Nurhikmah, Nurhikmah; Alam, Risma; Sundari, Sundari; Mawardi, Muh.; Sumai, Nhindi (Universitas Muhammadiyah Makassar, 2026)
This study aims to analyze the effectiveness of context-based Indonesian language learning in improving the literacy skills of the Kokoda community in Papua. The study is motivated by the low literacy levels influenced by the dominance of local languages, limited access to education, and the lack of learning approaches relevant to daily life contexts. This research employed a descriptive quantitative method combined with a community-based participatory approach (Community-Based Learning). The research design used a one-group pre-test–post-test model involving 45 participants from various age groups. Data were collected through literacy tests, observations, reflective interviews, and documentation, and analyzed using descriptive and inferential statistics. The results show that the initial literacy level of participants was categorized as low, with a mean score of 48.0. After the intervention, a significant improvement was observed, with the mean score increasing to 72.7. This improvement is supported by the paired sample t-test result (t = 12.45; p < 0.05), indicating statistical significance. In addition, participant engagement during the learning process was high, suggesting that the context-based approach effectively enhances motivation and participation. Therefore, context-based Indonesian language learning is proven to be effective in improving literacy skills and can be recommended as a strategic approach for literacy eradication and sustainable literacy development in local communities.